Salivary and serum proteomics in head and neck carcinomas before and after surgery and radiotherapy - Vidotto, A; Henrique, Tiago; Raposo, Luiz Sergio; Maniglia, José Victor; Silva, Eloiza Helena Tajara da [UNESP] (My University, 2011)
Several body fluids have been evaluated as new sources for cancer biomarker discovery. In this context, salivary and serum proteomics seem promising diagnostic and predictive tools for head and neck diseases. In the present study, we performed a proteomic analysis of saliva and serum from patients presenting head and neck squamous cell carcinoma (HNSCC) and compared the results before and after therapy. In saliva of cancer patients, we observed an altered protein profile, including over-expression of PLUNC and zinc-alpha-2-glycoprotein. Both proteins may contribute to control tumor growth and, therefore, represent targets for new analysis. We also detected serotransferrin and a modified transthyretin form with altered levels in serum from patients. Comparing preoperative and postreatment samples, the results showed that the protein profile after treatment reverted to a pattern closer to those observed for controls. These results add information on the role of secreted proteins in the cancer process and emphasize the potential of saliva and serum analysis for diagnosis and monitoring of HNSCC.